Acoustic frequency dependence of transmission characteristics in fiber acoustic gratings - Zhang, Hao; Liu, Bo; Tao, Junhao; Dong, Hongguang; Guo, Tieyan; Zhang, Meng (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
The dependence of transmission characteristics on acoustic frequency for an SMF-based acousto-optic tunable filter has been investigated in this paper. Experimental results indicate that multi-resonance peaks may turn up in the transmission spectrum when applied acoustic frequency is sufficiently high, and resonance wavelengths increase in proportion to the applied acoustic frequency for short resonance wavelength region, while they have opposite acoustic frequency responses for longer resonance wavelength region. Our numerical simulation proves that this phenomenon could be attributed to the non-monotonic phase matching curves of acoustic gratings, which would be helpful for the understanding of mode coupling mechanism in fiber acoustic gratings and design of fiber-based acousto-optic devices.
Optica Applicata, Vol. 41, 2011, Nr 4, s. 817-823
Keywords: optyka; acousto-optic tunable filter (AOTF); acousto-optic mode coupling; single-mode fiber (SMF); long period grating (LPG); acoustic grating